2004
DOI: 10.1111/j.1523-1755.2004.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between level of adult blood pressure and nephron number or renal filtration surface area?

Abstract: There is not a direct corollary between nephron number or renal FSA and level of blood pressure in this rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…Compensating for a reduction in glomerular number by hypertrophy of the glomeruli is a finding consistent with the data of others (Nagata et al, 1992;Nyengaard, 1993;Black et al, 2004). The compensation of filtration capacity following a reduction in glomerular number by an increase in glomerular size, however, is not always seen in the foetal or early postnatal kidney, suggesting that filtration is sufficient for the body size at this age, even in animals with fewer glomeruli (Zohdi et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Compensating for a reduction in glomerular number by hypertrophy of the glomeruli is a finding consistent with the data of others (Nagata et al, 1992;Nyengaard, 1993;Black et al, 2004). The compensation of filtration capacity following a reduction in glomerular number by an increase in glomerular size, however, is not always seen in the foetal or early postnatal kidney, suggesting that filtration is sufficient for the body size at this age, even in animals with fewer glomeruli (Zohdi et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, hypertension induced by decreased placental perfusion in the rat did not result in decreased GFR at 8 wk of age (34), and studies by one of the authors have shown normal nephron number and GFR in rats that were made hypertensive by high maternal dietary sodium (27). Thus, although the hypertension has been suggested to result directly from impaired Na filtration as a result of reduced nephron count and GFR, the mechanism may be more complex and involve other renal mechanisms (107). Furthermore, the mechanisms of programming for hypertension may not be identical in different models.…”
Section: Targets Of Programming In the Fetusmentioning
confidence: 99%
“…The number of nephrons within the fixed kidneys was estimated using an unbiased physical disector/fractionator technique as previously described [5,21].…”
Section: Animal Treatmentmentioning
confidence: 99%